Accountability in EU decision-making at the national level - Lajh, Damjan (Teorija in praksa, 2017)
This article considers accountability in decision-making on EU affairs at the Slovenian national level from the constitutional and democratic perspectives. Its scope is limited to the coordination of EU affairs and the formation of national positions on selected legislative proposals of the European Commission, with an emphasis on scrutiny over the executive by National Assembly and civil society organisations (CSOs). It further argues that, in the case of Slovenia, we can determine established accountability arrangements which are accompanied by a dysfunctional accumulation of a range of accountability mechanisms: a bias in favour of the executive power; exclusion of CSOs from the process of EU decision-making at the national level; and passiveness on the part of the National Assembly and CSOs.
Keywords: Civil society; Civilna družba; European Union; Evropska unija; Executive power; Izvršna oblast; Legislative power; Odgovornost; Political decision making; Politično odločanje; Responsibility; Slovenia; Slovenija; Zakonodajna oblast